TEMPORAL TRANSFORMATION IN SPACE DWELLINGS OF MOSLEM PEOPLE RELIGIOUS TOURISM (Case: Kampung Mahmud, Mekar Rahayu Village Kecamatan Marga Asih - Kabupaten Bandung) - Susanti, Indah
This study aimed to identify the changes of dwelling space based on the activity, space function, space layout, space dimension, space user, and territory during the event of religious tourism in the Kampung Mahmud settlement of Bandung Regency. The motivated phenomenon of this study is that dwelling on a settlement always change in a certain period, which is related with time and human activity. That change is a process in adapting and responding to human needs over the space to move. The entry and development of religious tourism in the form of moslem pilgrimage activities and organization into settlement give effect to changes the environment of space settlements, especially in some dwellings. That caused by the need for the provision of tourist facilities and the change/transition of the dwellings space use during the religious tourism. Observations of that changes, seen under conditions when the daily dwelling space (low season) and current events (peak season) that is temporary. This study uses quantitative and qualitative methods (Mixed Methods). In analyzing that change begins with the translation of the qualitative data that describes the current space condition daily (low season) and elaboration of the existence of the tourism component. Then the data on space changes that has been obtained from the interviews were analyzing first using distribution analysis by JMP program, aimed to obtain the highest frequency of space changes and to determine the varians of the space changes category based on the variables that observed. After that, a correlation analysis to determine the relationship between variables. Then from the results of the quantitative data on space changes aided also by qualitative descriptive analysis. The existing data of space changes then compared with the daily space condition data, then analyzed, interpreted descriptively and adjusted to the transformation theory. From 100 dwellings that has interviewed, there are 75 dwellings has changed and 25 dwellings has not. Space changes, mostly happen in aspect of the activity (72 dwellings), function (71 dwellings), users (70 dwellings), and territories (51 dwellings). The entry of religious tourism elements in this village reflects the commercial function in the majority of dwellings, that cues by the highest changes in trading activity, that is open stalls in a particular space on their dwellings. The results of this study indicate the change that has occurred in Kampung Mahmud has some varians of changes based on the degree of change, some changes in small portion, some changed largely and some changed totally in their dwellings based on activity, function, layout, dimensions, user, and territories aspects. The space changes occurred temporarily, only during religious events and return to normal in daily life, depicting a metamorphosis that repeated in each period. It shows the temporal transformation is a space transfiguration that occurs due to religious tourism activity.